Caregiver‐reported executive functioning and associated adaptive and challenging behaviour in children with histories of developmental delay. Issue 1 (2nd July 2021) - Barton, H.; McIntyre, L. L.
Abstract: Background: Deficits in executive functioning (EF) have been measured in individuals with developmental disabilities, such as autism spectrum disorder and attention‐deficit/hyperactivity disorder, through the use of behaviour rating scales and performance‐based assessment. Associations between EF and variables such as challenging and adaptive behaviour have been observed; however, limited research exists on EF profiles in children with heterogeneous developmental delay or with intellectual disability (ID) or the impact of EF on adaptive and challenging behaviour with this population. Methods: The present study sought to examine the EF profile of 93 children (75 male and 18 female) previously identified with developmental delay in early childhood. EF was assessed using the Behaviour Rating Inventory of Executive Function, Second Edition (BRIEF‐2). Children were categorised into an ID group ( n  = 14) or no ID group ( n  = 79) based on scores from cognitive and adaptive behaviour assessments. EF profiles were investigated and compared by group. In addition, the impact of EF on both adaptive behaviour and challenging behaviour was measured using hierarchical linear regressions. Results: Statistically significant differences in caregiver‐reported EF were not observed between groups; however, both the ID and the no ID group scores were elevated as reported by their caregivers. For the overall sample, caregiver‐EF accounted for significant variance in both adaptive (22%) and challenging (68%) behaviour after accounting for child age and sex. Conclusions: Results indicated deficits in EF for children with and without ID. The significance of EF was accounted for in both adaptive and challenging behaviour for all children in the sample. Future research could elucidate the role of adaptive and challenging behaviour in understanding EF variability among children with histories of developmental delay.